RESEÑA de: Belloch, Amparo; Sandín, Bonifacio; Ramos, Francisco. Manual de Psicopatología. Vols. 1 y 2. Madrid : McGraw Hill/Interamericana, 1995 - Olabarría, Begoña (Revista de Psicopatología y Psicología Clínica, 1996)
-